The Association of COVID-19 Degree on Transamination and Bilirubin Levels of COVID-19 Patients in RSUD Dr. Saiful Anwar Malang - Ade Rahmawati; Syifa Mustika (Clinical and Research Journal in Internal Medicine, 2022)
Background : Corona virus 2019 (COVID-19) is an infectious viral disease caused by SARS-CoV-2 that has infected the world. COVID-19 can cause abnormalities which are characterized by increased levels of the enzyme transaminase and bilirubin. Research on the association between transaminase enzymes and bilirubin is still limited, further research is needed on the association between the degree of COVID-19 and levels of the transaminases and bilirubin enzymes. Aim: To determine the association between liver function on the degree of severity and outcome of COVID-19 patients. Method: This was the cross-sectional study. Sampling method was using consecutive sampling at RSUD Dr. Saiful Anwar Malangwho was treated from June 1st 2021 until November 31st 2021 by the Department of Internal Medicine. Statistical analysis used the Kruskal Walllis and Mann Whitney test with a significance level of p<0.5% and correlation analysis using Spearman. Result: Among 90 patients included in this study there was a strong positive correlation between the degree of COVID-19 and levels of SGOT (r=0.954, p <0.001) and SGPT (r=0.727, p <0.001) and according to regression test, SGOT has the positive correlation towards degree of COVID-19 severity (p=0.026 CI95%: 0.002-0.028). There was a correlation between the degree of COVID-19 and the total bilirubin level (r=0.586, p=0.011). There was no correlation between levels of transaminase enzymes, total bilirubin, direct and indirect bilirubin on the patient's outcome (p>0.050). Conclusion: There is a positive correlation between the degree of COVID-19 with levels of the enzyme transaminases, indirect and total bilirubin.